BASIS OF IMPLEMENTATION OF RESOURCE-EFFECTIVE SHAFT PRODUCTION - Obidov, Avazbek; Abdurasulov, Axror (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Increasing energy efficiency in the cotton industry is one of the pressing issues. This article presents the results of research aimed at reducing energy consumption during the operation of a cotton 5LP linter machine. The issues of creating and refining methods for calculating high-performance machine drives and shafts are of particular importance in creating machines for the cotton ginning industry. The article shows that the task of reducing the mass of the main working body of the linter, the sawn cylinder shaft, was performed by grooving and slotting, and the design features of the resource-saving shaft are determined.